User centric metrics for a realistic assessment of broadband services - Popoviciu, Ciprian (Frontiers in Communications and Networks, 2023)
Past broadband adoption initiatives underscored common wisdom: "We cannot manage what we cannot accurately measure", "Trust but verify". Self-reported FCC data has been notoriously unreliable or lacking granularity and that led to an overoptimistic perception of the quality and coverage of broadband services. Data collected in the past was deficient in providing a complete view of the user experience by focusing exclusively on a simple metric, bandwidth availability. Moreover, data collected in the past typically provided a point-in-time perspective on the state of broadband services in each region. In this paper, we discuss a new set of metrics and measurement techniques needed to make broadband funding decisions efficient in terms of quality of services delivered and return on investment, and to track their progress. We propose composite metrics that capture the complete value of the service to the user and emphasize the feasibility of measuring and monitoring such a metric over time. This is a provisional file, not the final typeset article Modern K-12 and Higher-Ed education is more and more dependent on internet resources, from collaboration tools to educational resources, and administrative processes. Access to the Internet is critical to the success of students at all levels of their education. Middle and high school students with high-speed Internet access at home have more digital skills, higher grades, and perform better on standardized tests, such as the SAT and are more likely to attend college or university [9]. Higher education requires access to high-speed internet for class and project participation and for homework submissions. All the opportunities provided and needs met by broadband access were underlined by the COVID-19 pandemic [10]. Households without quality or even basic broadband access faced significant challenges in negotiating quarantine constraints. During the COVID-19 pandemic, the digital divide between those who have and does who do not have broadband access at home was clearly underlined.